Epidemiology of Alzheimer’s Disease and Dementia in Arab Countries: A Systematic Review - Ashraf El-Metwally; Paivi Toivola; Mashael Al-Rashidi; Shanila Nooruddin; Munazza Jawed; Raghad AlKanhal; Hira Abdul Razzak; Nada Albawardi (Behavioural Neurology)
Background/Objectives. Contrary to popular belief, the condition of dementia is not an actual discrete disease, but rather a group of symptoms, most notable of which is the disturbance of memory and social ability, often severe enough to impair daily functioning. As a result, it has been a major cause of functional deterioration among varying populations in the world. This study is aimed at reviewing the epidemiology of dementia in Arab countries in terms of its prevalence, distribution, and risk factors. Methods. A systematic literature review was conducted using articles published in PubMed, Embase, Scopus, and other local journals between 1990 and 2018. After applying the inclusion and exclusion criteria, a total of 18 studies were concluded to be eligible for the review. Results. Prevalence studies demonstrated that dementia is indeed a prevalent condition in Arab countries, ranging between 1.1% and 2.3% among age groups of 50 years and older, as well as between 13.5% and 18.5% among age groups of 80 years and above. However, these results are not different from those of many other countries in the world. Moreover, prevalence was found to vary depending on sociodemographic characteristics. Major risk factors of dementia included hypertension, low income, and low education, while the risk of developing dementia is increased by obesity, diabetes mellitus, and cardiovascular risk factors. Despite the growing evidence regarding the epidemiological distribution and determinants of dementia worldwide, studies from the Arab region remain scarce. Conclusion. This systematic review highlights the need for population-based studies to provide necessary information for developing preventive and curative strategies specific to the Arab region.